Consumer Purchase Intention in Environmentally And Digitally Wedding Service During Covid-19 Pandemic (Journal of Business and Management, 2022)
Abstract. Wedding celebrations in Indonesia usually invite many people and each guest can contribute at least one to three trash and become a contributor to waste just from the activity that lasts for around 3 hours. Along with this, the Covid-19 pandemic has had a significant impact on consumer habits and behavior in particular because the pandemic has had such a large impact on people's daily life one of them is weddings. The purpose of this study is to investigate factors that influence digital wedding service using Extended Technology Acceptance Model. The study used quantitative research to analyze the Technology Acceptance Model incorporated with Environmental Knowledge and Impact of Covid -19 using Structural Equation Model by using the RStudio software. The result is perceived ease of use significant to perceived usefulness. Perceived usefulness, perceived ease of use, and impact of Covid- 19 are significant to attitude towards using digital wedding service in Indonesia. And the factor that affects purchase intention is environmental knowledge and attitude towards using digital wedding service. These findings can generate more suitable practical implications to promote digital wedding service in Indonesia during the current and post-pandemic periods.Keywords: Digital wedding, Environment, Covid-19, Technology Acceptance Model (TAM)